Trees, stolen gods, and becoming Egyptian: Reading Genesis missionally. Issue 4 (October 2022) - Tompkins, Andrew
This article attempts to add to missiological discussions by rereading some selected passages from the life of Abraham, Jacob, and Joseph using a missional hermeneutic. I have chosen Genesis 12:6–7 and 13:18, which record Abraham's forms of worship and dwelling among important groves of trees, as a potential example of worshipping God in a plural society in the public sphere and as a potentially helpful example for worshipping God today in the public sphere. I then turn to the struggle of Jacob and his family's connection to deities other than Yahweh in their journey away from Laban toward God found in Genesis 31:19, 32, and 35:2–4. The final part of this article will discuss Joseph in Egypt, more specifically his full acceptance as an Egyptian as found in Genesis 41:45, 50; 42:8; 43:32 and his use and practice of Egyptian rituals as a part of his daily life as demonstrated in Genesis 44:5, 15, and 44:31–34. I hope this article will on the missiological issues presented as well as on the potential of Genesis to inform the ongoing discussions of missiology, especially in the construction of robust biblically faithful theology of mission work. Reading the Bible from a missional hermeneutic is a relatively new hermeneutical phenomenon that is still in the process of development. This article is one version of how this hermeneutic can aid biblical studies and how missiological studies can reread the text in meaningful ways.